THE RELATIONSHIP BETWEEN SINGLE MOTHER STATUS AND THE NUMBER OF CHILDREN WITH THE RATE OF DEPRESSION OF SINGLE MOTHERS IN BANYUMAS - Triana, Noor Yunida; Apriliyani, Ita (HEARTY, 2026)
Single mothers have dual responsibilities as breadwinners as well as primary caregivers. This can trigger chronic stress and end up in depressive disorders. There are several factors that cause depressive disorders in single mothers, including the status of single mothers and the number of children who are responsible. The purpose of this study is to determine the relationship between single mother status and the number of children with the level of depression in single mothers in Banyumas. This research method uses correlational quantitative research with a cross-sectional approach. The instruments used were the DASS questionnaire that had been tested for validity (r = 0.312 – 0.784) and reliability test (Cronbach’s alpha ≥ 0.80). Data analysis using the Spearman rank test. The results of the study showed that the status of single mothers in Banyumas was mostly in the living divorce group of 56.3% (27 respondents), the number of children mostly in the category of double children was 77.08% (37 respondents). The rate of single mother depression was mostly in the mild category of 54.16% (26 respondents). There was a relationship between single mother status and depression level with a p value of 0.001 < 0.05 and there was a relationship between the number of children and depression level with a p value of 0.004 < 0.05.